2014
DOI: 10.1136/bcr-2014-207238
|View full text |Cite
|
Sign up to set email alerts
|

Venous sinus thrombosis secondary to tuberculous meningitis: a novel cause of trigeminal neuralgia

Abstract: A 33-year-old Vietnamese man with a history of superior sagittal sinus thrombosis secondary to tuberculous meningitis presented with severe recurrent trigeminal neuralgia. A complex compensatory cerebral venous drainage system developed, and a varix, in direct contact with the root entry zone of the trigeminal nerve, was the trigger for his pain. The patient's symptoms are presently controlled with a combination of medications for neuropathic pain, however he continues to experience frequent severe exacerbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In CVT, when the V nerve is involved, symptoms can manifest as trigeminal neuralgia. Tsimiklis et al ( 2014 ) reported a 33-year-old female with a history of superior sagittal sinus thrombosis characterized by severe recurrent trigeminal neuralgia. An examination revealed that this neuralgia was caused by varicose veins that had compressed the trigeminal nerve.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In CVT, when the V nerve is involved, symptoms can manifest as trigeminal neuralgia. Tsimiklis et al ( 2014 ) reported a 33-year-old female with a history of superior sagittal sinus thrombosis characterized by severe recurrent trigeminal neuralgia. An examination revealed that this neuralgia was caused by varicose veins that had compressed the trigeminal nerve.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[28] Isolated sixth nerve palsy without intracranial hypertension has been reported with inferior petrosal sinus thrombosis[35] and transverse sinus thrombosis. [36] Isolated trigeminal neuropathy[37] and facial neuropathy[3839] have also been reported. In a study by Duman et al ,[20] cranial nerve palsies were detected in 11% of patients with CVST.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Leiden mutation of coagulation factor V is the most common cause of hereditary thrombosis. The decrease of anticoagulants and the increase of procoagulant factor (mainly factor V III) activity in patients with TBM lead to blood hypercoagulability and thrombosis [ 10 ]. In addition, TBM directly compresses the venous sinus by forming granulation tissue or abscess, and it can also lead to thrombosis by changing hemodynamics [ 11 ].…”
Section: Intracranial Venous Thrombosismentioning
confidence: 99%